Children and childhood in world religions : primary sources and texts - Browning, Don S.; Bunge, Marcia J. (Marcia JoAnn), 1954- (Rutgers series in childhood studies., 2009)
"While children figure prominently in religious traditions, few books have directly explored the complex relationships between children and religion. This is the first book to examine the theme of children in major religions of the world. Each of six chapters, edited by world-class scholars, focuses on one religious tradition and includes an introduction and a selection of primary texts ranging from legal to liturgical and from the ancient to the contemporary. Through both the scholarly introductions and the primary sources, this comprehensive volume addresses a range of topics, from the sanctity of birth to a child's relationship to evil, showing that issues regarding children are central to understanding world religions and raising significant questions about our own conceptions of children today"--Publisher description.